Efficacy of Laparoscopic-Assisted Subcostal Transversus Abdominis Plane (TAP) Block: A Double-Blind, Randomized Controlled Trial - Sadaf Ishaque; Sarmad Masud; Rizwan Ahmed Khan; Nauman Ismat Butt (Journal of Bahria University Medical and Dental College, 2024)
Objective: To analyze efficacy of laparoscopic administered Transversus Abdominis Plane (TAP) block on pain scores and opioid consumption in the first 24 hours in patients undergoing laparoscopic cholecystectomy. Study design and setting: The randomized, double-blinded trial was conducted in surgical unit, Shalamar Medical & Dental College Lahore from September 2019 to March 2020. Methodology: 100 patients of either gender scheduled for elective laparoscopic cholecystectomy were included using consecutive probability sampling method. After informed consent, patients were randomized into Intervention TAP GroupA and Control Group-B. Intervention TAP Group-A received laparoscopic aided TAP block with 20ml 0.5% Ropivacaine in subcostal region while Control Group-B received 20ml saline solution which was used as placebo. Both groups received paracetamol 1gm intravenous eight-hourly and Ketorolac 30mg intravenous 12-hourly. Nalbuphine 5mg intravenous was administered as “rescue analgesic” in patients having pain score of four or above. Postoperative pain scores at rest and on coughing were documented using numerical rating scores (VAS) at 2, 4, 6, 12, and 24 hours. Results: There was a significant difference (p-value=0.038, 0.000, 0.025, 0.000, 0.000) in pain scores over the first 24 hours postoperatively in laparoscopically assisted Intervention TAP Group-A. The total nalbuphine consumption was significantly reduced in Intervention TAP Group-A as compared to Control Group-B. Conclusions: Laparoscopic administered TAP block significantly reduced postoperative pain and total opioid consumption following laparoscopic cholecystectomy